2018
DOI: 10.1021/acs.langmuir.8b03448
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Thermotropic Ionic Liquid Crystals Formed via Self-Assembled Zwitterionic Ionic Liquids

Abstract: Supramolecular thermotropic ionic liquid crystals (ILCs) with hexagonal and lamellar phases were fabricated by the self-assembly of zwitterionic ionic liquids, which were formed by 3-(1-alkyl-3-imidazolio) propanesulfonate with different alkyl chain lengths C n IPS (n = 12, 14, 16) and 3,4,5-tris(dodecyloxy)benzoic acid (TDBA) based on intermolecular electrostatic interactions. The phase behaviors of ILCs were investigated by differential scanning calorimetry (DSC), small-angle X-ray scattering (SAXS), and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In 47 / 48 , it was postulated that the proton-conducting pathways were formed by the H-bonded dimers of 47 that were bridged with 48 . Similarly, Zheng et al reported the thermotropic ILCs with Col h and Sm phases capable of conducting protons under anhydrous conditions . These ILCs were constructed from imidazolium-based amphiphilic zwitterions and 3,4,5-dodecyloxybenzoic acid through intermolecular electrostatic interactions.…”
Section: Nanostructured Ionic Liquid Crystals For the Conduction Of I...mentioning
confidence: 97%
See 1 more Smart Citation
“…In 47 / 48 , it was postulated that the proton-conducting pathways were formed by the H-bonded dimers of 47 that were bridged with 48 . Similarly, Zheng et al reported the thermotropic ILCs with Col h and Sm phases capable of conducting protons under anhydrous conditions . These ILCs were constructed from imidazolium-based amphiphilic zwitterions and 3,4,5-dodecyloxybenzoic acid through intermolecular electrostatic interactions.…”
Section: Nanostructured Ionic Liquid Crystals For the Conduction Of I...mentioning
confidence: 97%
“…Similarly, Zheng et al reported the thermotropic ILCs with Col h and Sm phases capable of conducting protons under anhydrous conditions. 99 These ILCs were constructed from imidazolium-based amphiphilic zwitterions and 3,4,5-dodecyloxybenzoic acid through intermolecular electrostatic interactions. The imidazolium zwitterions played an important role in the formation of LC phases with highly ordered and well-defined ion-conducting pathways, thus resulting in higher ionic conductivities compared to that of 3,4,5-dodecyloxybenzoic acid itself.…”
Section: The Conduction Of Ions and Protonsmentioning
confidence: 99%
“…The protons residing in the alkyl chain ((CH2)n) in all compounds 12aza and 14aza' chain can be substantiated by multiples at the range of δ =2.46-1.09 ppm. Moreover, a signal which appears as triplet at the chemical shift δ =0.88-0.80 ppm can be assigned to the terminal methyl (CH3) [14,15]. The data of the 13 C-NMR chemical shifts for title compounds 6aza-14aza and 6aza'-14aza' in DMSO solution are listed in respective Tables 5 and 6.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the possibilities of ionic interactions in low-molecular weight molecular self-assemblies have recently become appreciated in the perspective of ionic liquid crystals 8,[19][20][21][22][23][24][25][26][27][28] . A particular case deals using zwitterions with bound positive and negative charges in the compounds, i.e., involving no counter-ions [29][30][31][32][33][34][35] . Therein, the long-range electrostatic interactions of ionic groups facilitate liquid crystallinity instead of the shape persistent mesogens.…”
Section: Introductionmentioning
confidence: 99%